A kind of high conductivity and high adhesion carbon-coated aluminum foil and preparation method thereof

By improving the conductive agent components, a high-conductivity and high adhesion carbon-coated aluminum foil was prepared, which solved the problem of insufficient conductivity and adhesion of traditional carbon-coated aluminum foils, and significantly improved the conductivity and service life of lithium batteries.

CN119742371AInactive Publication Date: 2025-04-01合肥源元科技股份有限公司

Patent Information

Application Number
CN202411920152.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The conductive properties and adhesion of traditional carbon-coated aluminum foils are insufficient, and cannot meet the requirements of new energy vehicle batteries for high conductivity and high adhesion.

Method used

By improving the conductive agent components, a conductive paste composed of carbon-based conductive carbon black, conductive additives, binders, additives and solvents was prepared, and then coated on the surface of the aluminum foil substrate and cured to form a carbon-coated aluminum foil with high conductivity and high adhesion.

Benefits of technology

It significantly reduces the resistance of carbon-coated aluminum foil for lithium batteries, improves its conductive properties, and increases the bonding force with the positive electrode active material of lithium batteries, extending the service life of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742371A_ABST
    Figure CN119742371A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of current collectors, specifically to a carbon-coated aluminum foil with high conductivity and high adhesion and a preparation method thereof, wherein the carbon-coated aluminum foil comprises an aluminum foil substrate and a carbon-coated layer, the carbon-coated layer is obtained by curing after applying a conductive slurry to the surface of the aluminum foil substrate, and the conductive slurry is prepared by the following components in parts by weight: 6-7.5 parts of carbon-based conductive carbon black, 0.5-2 parts of conductive additives, 25-30 parts of binders, 0.5-1 parts of auxiliary agents, and 61-66.5 parts of solvents. The present invention improves the conductive agent component to obtain a carbon-coated aluminum foil with excellent performance, the resistivity is controlled at 0.02-0.1Ω·m, and the bonding range between the carbon-coated aluminum foil and the positive active material of the lithium battery is controlled at 300-400mN / mm. Through the synergistic promotion between the raw materials, the resistance is significantly reduced, the conductive performance is improved, the contact area between the positive active material and the carbon-coated layer is increased, and the bonding between the carbon-coated aluminum foil and the positive active material of the lithium battery is improved, thereby improving the conductive performance of the lithium battery, extending the service life, and meeting market demand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of current collectors, and in particular to a carbon-coated aluminum foil with high conductivity and high adhesion and a preparation method thereof. Background Art

[0002] With the development of the new energy vehicle field, enterprises in the industry have higher and higher requirements for power vehicle batteries. Lithium batteries are widely used due to their high cycle performance, high safety and pollution-free. Lithium batteries are a kind of recyclable battery that relies on the movement of lithium ions between the positive electrode and the negative electrode to realize the charging and discharging process. The positive electrode current collector substrate of lithium batteries is aluminum foil, but the use of aluminum foil has problems such as insufficient bonding force with the positive electrode active material and high contact resistance. In view of some problems existing in the traditional positive electrode current collector, a layer of conductive slurry is evenly coated on the surface of the aluminum foil to make carbon-coated aluminum foil, which can be solved. Carbon-coated aluminum foil has the advantages of significantly improving the consistency of the battery pack, improving the bonding adhesion between the active material and the current collector, and protecting the current collector to extend the battery life.

[0003] The conductive slurry used in carbon-coated aluminum foil is usually a composite slurry mainly composed of conductive carbon. The conductivity provided by the conductive carbon black in the traditional conductive slurry conductive system can no longer meet the requirements of the existing current collector. In addition, because its single-component conductive carbon black forms a dense coating on the substrate surface with a low surface roughness, the adhesion between the carbon-coated aluminum foil and the positive electrode active material can no longer meet the requirements of the currently developing battery process. Therefore, it is urgent to develop a carbon-coated aluminum foil with better conductivity and stronger adhesion to lithium battery electrode materials. Summary of the invention

[0004] The purpose of the present invention is to provide a carbon-coated aluminum foil with high conductivity and high adhesion and a preparation method thereof. The carbon-coated aluminum foil has good conductivity and excellent adhesion with the positive electrode active material of the lithium battery, effectively solving the technical problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions.

[0006] A carbon-coated aluminum foil with high conductivity and high adhesion, comprising an aluminum foil substrate and a carbon-coated layer, wherein the carbon-coated layer is obtained by coating a conductive slurry on the surface of the aluminum foil substrate and then curing the conductive slurry, and the conductive slurry is prepared from the following components in parts by weight: 6-7.5 parts of carbon-based conductive carbon black, 0.5-2 parts of a conductive additive, 25-30 parts of a binder, 0.5-1 parts of an auxiliary agent, and 61-66.5 parts of a solvent.

[0007] Preferably, the carbon-based conductive black is at least one of acetylene black and Ketjen black.

[0008] Preferably, the conductive additive is at least one of graphene and single-walled carbon nanotubes.

[0009] Preferably, the binder is polyacrylic acid and modified resins thereof.

[0010] Preferably, the auxiliary agent is at least one of a cationic wetting and dispersing agent, an anionic dispersing agent and a polymer wetting agent.

[0011] Preferably, the solvent consists of water and an organic solvent, and the mass ratio of water to the organic solvent is 3-5:1.

[0012] Preferably, the organic solvent is at least one of isopropanol and n-propanol.

[0013] By improving the conductive agent component, a carbon-coated aluminum foil with excellent performance is prepared. The resistivity of the carbon-coated aluminum foil prepared by the present invention is controlled at 0.02-0.1Ω·m, and the bonding force between the carbon-coated aluminum foil and the positive electrode active material of the lithium battery is controlled in the range of 300-400mN / mm. The surface of the prepared carbon-coated aluminum foil is fine and uniform without obvious defects, and has good industrialization potential.

[0014] The present invention also provides a method for preparing a carbon-coated aluminum foil with high conductivity and high adhesion, which specifically comprises the following steps:

[0015] Step 1: Add corresponding amounts of carbon-based conductive carbon black and conductive additives, add corresponding amounts of additives and solvents into a mixing cylinder, stir at a speed of 800 rpm for 1-1.5 hours, and then mix the slurry I;

[0016] Step 2: Add corresponding amounts of carbon-based conductive carbon black and binder to the mixed slurry I, premix and stir at a speed of 1000 rpm until the mixture is uniformly mixed, then add the remaining solvent and mix at a speed of 1500 rpm, and finally grind to obtain a conductive slurry;

[0017] Step 3: Apply the conductive paste to the surface of the aluminum foil substrate and dry it at 80-150°C to obtain the carbon-coated aluminum foil.

[0018] The present invention significantly reduces the resistance of the carbon-coated aluminum foil for lithium batteries and improves its conductivity through the synergistic promotion effect between the various raw materials of the conductive slurry. At the same time, the contact area between the positive electrode active material and the carbon coating layer is increased, and the bonding force between the carbon-coated aluminum foil for lithium batteries and the positive electrode active material of the lithium battery is significantly improved, which helps to improve the conductivity of the lithium battery and extend its service life, meeting market demand.

[0019] The improved conductivity in the present invention comes from the compounded carbon-based conductive carbon black and conductive additives. By adding the conductive additives, the conductivity of the carbon-coated aluminum foil can be improved under the premise of slightly increasing the difficulty of dispersion. The addition of the dispersant also ensures the ability of the existing dispersion equipment to process the formula. The improved adhesion between the carbon-coated aluminum foil and the positive electrode active material in the present invention comes from the high surface roughness of the carbon-coated aluminum foil provided by the formula, which in turn provides a contact area between the carbon-coated layer and the positive electrode active material and increases the contact sites between the coatings. The binder in the positive electrode active material mostly uses PVDF, which results in the fact that most of its adhesion to the carbon-coated aluminum foil is provided by intermolecular forces. Improving the surface roughness of the carbon-coated aluminum foil will be beneficial to improving the anchoring ability of the positive electrode active material to the surface of the carbon-coated aluminum foil, thereby improving the adhesion, and better surface contact can improve the ion path, thereby improving the conductivity of the electrode sheet.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows.

[0021] 1. The present invention improves the conductive agent component to prepare a carbon-coated aluminum foil with excellent performance. The resistivity of the carbon-coated aluminum foil prepared by the present invention is controlled within the range of 0.02-0.1Ω·m, and the bonding force between the carbon-coated aluminum foil and the positive electrode active material of the lithium battery is controlled within the range of 300-400mN / mm. In addition, the surface of the carbon-coated aluminum foil prepared is fine and uniform without obvious defects, and has good industrialization potential.

[0022] 2. The present invention significantly reduces the resistance of the carbon-coated aluminum foil for lithium batteries and improves its conductivity through the synergistic promotion effect between the various raw materials of the conductive slurry. At the same time, it increases the contact area between the positive electrode active material and the carbon coating layer, and significantly improves the bonding force between the carbon-coated aluminum foil for lithium batteries and the positive electrode active material of the lithium battery, which helps to improve the conductivity of the lithium battery and extend its service life, meeting market demand.

[0023] 3. The improved conductivity in the present invention comes from the compounded carbon-based conductive carbon black and conductive additives. By adding conductive additives, the conductivity of the carbon-coated aluminum foil can be improved under the premise of slightly increasing the difficulty of dispersion. The addition of dispersants also ensures the ability of existing dispersing equipment to process the formulation.

[0024] 4. The improved adhesion between the carbon-coated aluminum foil and the positive electrode active material in the present invention comes from the high surface roughness of the carbon-coated aluminum foil provided by the formula, which in turn provides a contact area between the carbon-coated layer and the positive electrode active material and increases the contact sites between the coatings. The binder in the positive electrode active material mostly uses PVDF, which results in the fact that most of its adhesion to the carbon-coated aluminum foil is provided by intermolecular forces. Improving the surface roughness of the carbon-coated aluminum foil will be beneficial to improving the anchoring ability of the positive electrode active material to the surface of the carbon-coated aluminum foil, thereby improving the adhesion. In addition, better surface contact can improve the ion path, thereby improving the conductivity of the electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic cross-sectional view of a highly conductive and highly adhesive carbon-coated aluminum foil provided by the present invention;

[0026] Figure 2 A schematic diagram of the structural distribution of the high-conductivity and high-adhesion carbon-coated aluminum foil provided by the present invention;

[0027] Figure 3 The present invention provides a schematic flow chart of a method for preparing a highly conductive and highly adhesive carbon-coated aluminum foil.

[0028] In the figure: 1. Aluminum foil substrate; 2. Carbon coating layer. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] See also Figure 1 and Figure 2 The present invention provides a carbon-coated aluminum foil with high conductivity and high adhesion. The carbon-coated aluminum foil comprises an aluminum foil substrate 1 and a carbon-coated layer 2. The carbon-coated layer 2 is obtained by coating a conductive slurry on the surface of the aluminum foil substrate 1 and then curing the conductive slurry. The conductive slurry is prepared from the following components by weight: 6-7.5 parts of carbon-based conductive carbon black, 0.5-2 parts of conductive additives, 25-30 parts of binders, 0.5-1 parts of additives, and 61-66.5 parts of solvents.

[0031] Specifically, the carbon-based conductive carbon black is at least one of acetylene black and Ketjen black, the conductive additive is at least one of graphene and single-walled carbon nanotubes, the binder is polyacrylic acid and its modified resins, and the auxiliary agent is at least one of a cationic wetting dispersant, an anionic dispersant and a polymer wetting agent.

[0032] Specifically, the solvent consists of water and an organic solvent, the mass ratio of water to the organic solvent is 3-5:1, and the organic solvent is at least one of isopropanol and n-propanol.

[0033] See also Figure 3 The present invention also provides a method for preparing a carbon-coated aluminum foil with high conductivity and high adhesion, which specifically comprises the following steps:

[0034] Step 1: Add corresponding amounts of carbon-based conductive carbon black and conductive additives, add corresponding amounts of additives and solvents into a mixing cylinder, stir at a speed of 800 rpm for 1-1.5 hours, and then mix the slurry I;

[0035] Step 2: Add corresponding amounts of carbon-based conductive carbon black and binder to the mixed slurry I, premix and stir at a speed of 1000 rpm until the mixture is uniformly mixed, then add the remaining solvent and mix at a speed of 1500 rpm, and finally grind to obtain a conductive slurry;

[0036] Step 3: Coat the conductive paste on the surface of the aluminum foil substrate 1 and dry it at a temperature of 80-150° C. to obtain a carbon-coated aluminum foil.

[0037] The present invention is further described below in conjunction with examples so that those skilled in the art can better understand the present invention and implement it, but the examples are not intended to limit the present invention. In addition, the preparation processes in the following examples are conventional means in the prior art unless otherwise specified, and therefore, they will not be described in detail.

[0038] Example 1

[0039] 3 parts of acetylene black conductive carbon black, 1 part of graphene additive and 1 part of single-walled carbon nanotube additive were added into a planetary stirring slurry mixer, and then 1 part of an auxiliary agent, 30 parts of a binder and 30.5 parts of a solvent were added, and the mixture was stirred for 1.5 hours to obtain a mixed slurry I;

[0040] Add 3 parts of acetylene black conductive carbon black and the remaining solvent to the mixed slurry I, stir for 1.5 hours until uniform, and finally grind to obtain a conductive slurry, wherein the solvent is a mixture of deionized water and isopropanol in a mass ratio of 3:1;

[0041] The conductive slurry is then transfer-coated on the surface of the aluminum foil substrate 1 and dried at 110 degrees Celsius to obtain a carbon-coated aluminum foil for lithium batteries.

[0042] Example 2

[0043] 3.75 parts of Ketjen black conductive carbon black and 0.5 parts of single-walled carbon nanotube additives were added into a planetary mixing slurry mixer, and then 0.5 parts of an auxiliary agent, 25 parts of a binder and 33.25 parts of a solvent were added, and the mixture was stirred for 1 hour to obtain a mixed slurry I;

[0044] 3.75 parts of conductive carbon black and the remaining solvent were added to the mixed slurry I, and the mixture was stirred for 1 hour until uniform. Finally, the conductive slurry was obtained after grinding, wherein the solvent was a mixture of deionized water and isopropanol in a mass ratio of 3:1;

[0045] The conductive slurry is transfer coated on the surface of the aluminum foil substrate 1 and dried at 110 degrees Celsius to obtain a carbon-coated aluminum foil for lithium batteries.

[0046] Example 3

[0047] 3.5 parts of acetylene black conductive carbon black and 1 part of graphene additive were added into a planetary mixing slurry machine, and then 0.75 parts of auxiliary agent, 27.5 parts of binder and 32.5 parts of solvent were added, and the slurry was mixed after stirring for 1 hour;

[0048] Add 3.5 parts of conductive carbon black and the remaining solvent to the mixed slurry I, stir for 1 hour until uniform, and finally grind to obtain a conductive slurry, wherein the solvent is a mixture of deionized water and n-propanol in a mass ratio of 5:1;

[0049] The conductive slurry is transfer coated on the surface of the aluminum foil substrate 1 and dried at 110 degrees Celsius to obtain a carbon-coated aluminum foil for lithium batteries.

[0050] Example 4

[0051] 3.25 parts of Ketjen black conductive carbon black and 1.5 parts of single-walled carbon nanotube additives were added into a planetary mixing slurry mixer, and then 0.7 parts of an auxiliary agent, 28 parts of a binder and 31.65 parts of a solvent were added, and the mixture was stirred for 1.5 hours to obtain a mixed slurry I;

[0052] 3.25 parts of conductive carbon black and the remaining solvent were added to the mixed slurry I, and the mixture was stirred for 1 hour until uniform. Finally, the conductive slurry was obtained after grinding, wherein the solvent was a mixture of deionized water and n-propanol in a mass ratio of 4:1;

[0053] The conductive slurry is transfer coated on the surface of the aluminum foil substrate 1 and dried at 110 degrees Celsius to obtain a carbon-coated aluminum foil for lithium batteries.

[0054] Example 5

[0055] 3.25 parts of acetylene black conductive carbon black and 1.5 parts of single-walled carbon nanotube additives were added into a planetary mixing slurry mixer, and then 0.5 parts of an auxiliary agent, 30 parts of a binder and 30.75 parts of a solvent were added, and the mixture was stirred for 1 hour to obtain a mixed slurry I;

[0056] Add 3.25 parts of conductive carbon black and the remaining solvent to the mixed slurry I, stir for 1 hour until uniform, and finally grind to obtain a conductive slurry, wherein the solvent is a mixture of deionized water: n-propanol: isopropanol in a mass ratio of 3:1:1;

[0057] The conductive slurry is transfer coated on the surface of the aluminum foil substrate 1 and dried at 110 degrees Celsius to obtain a carbon-coated aluminum foil for lithium batteries.

[0058] Three comparative examples are listed below for better comparison with the embodiment. The specific comparative examples are as follows:

[0059] Comparative Example 1

[0060] Compared with Example 1, the difference of Comparative Example 1 is that the conductive additive component is changed to conductive carbon black, and the other processes are the same as those of Example 1.

[0061] Comparative Example 2

[0062] Compared with Example 2, the difference of Comparative Example 2 is that the conductive additive component is changed to conductive carbon black, and the other processes are the same as those of Example 2.

[0063] Comparative Example 3

[0064] Compared with Example 3, the difference of Comparative Example 3 is that the conductive additive component is changed to conductive carbon black, and the other processes are the same as those of Example 3.

[0065] Performance testing

[0066] The following performance tests were performed on the eight types of carbon-coated aluminum foils for lithium batteries prepared in Examples 1-5 and Comparative Examples 1-3:

[0067] Peel strength: LiFePO4 cathode slurry was coated on the above eight types of carbon-coated aluminum foils for lithium batteries in turn, and each of them was made into a surface density of 344 g / m 2 , compacted density is 2.3g / cm 3 The electrode was tested for peeling strength using a 180° peeling 3M tape test method. The test results are shown in Table 1 below.

[0068] Resistance to electrolyte wiping: Use a cotton swab to dip the electrolyte and wipe the eight types of carbon-coated aluminum foils for lithium batteries according to the standard wiping times to test the resistance to electrolyte wiping times. The test results are shown in Table 1 below;

[0069] Diaphragm resistance: The resistance of the eight types of carbon-coated aluminum foils for lithium batteries was tested using a diaphragm resistance tester. The test results are shown in Table 1 below.

[0070] Surface roughness: The surface roughness of the eight types of carbon-coated aluminum foils for lithium batteries was tested using a roughness tester. The test results are shown in Table 1 below.

[0071]

[0072] Table 1 Performance test results of eight kinds of carbon-coated aluminum foil for lithium batteries

[0073] It can be seen from Table 1 that the carbon-coated aluminum foil for lithium batteries of the present application has a lower resistance and a stronger bonding force with the positive active material of the lithium battery. The resistivity range of the carbon-coated aluminum foil for lithium batteries is 0.05-0.15Ω·m, and the bonding force range between the carbon-coated aluminum foil and the positive active material of the lithium battery is 340-400mN / mm. The prepared carbon-coated aluminum foil for lithium batteries has a fine and uniform surface without obvious defects. Compared with competing products on the market, the carbon-coated aluminum foil prepared by the patented method has a slightly higher surface roughness, membrane resistivity and peel strength.

[0074] In the present application, through the synergistic promotion effect between the various raw materials of the conductive slurry, the resistance of the carbon-coated aluminum foil for lithium batteries is significantly reduced, and its conductive performance is improved. At the same time, the contact area between the positive electrode active material and the carbon-coated layer 2 is increased, and the bonding force between the carbon-coated aluminum foil for lithium batteries and the positive electrode active material of the lithium battery is significantly improved, which helps to improve the conductive performance of the lithium battery and extend its service life, which meets market demand.

[0075] By comparing Examples 1-5 with Comparative Examples 1-3, it can be seen that the conductive additive can effectively increase the conductive properties of the carbon-coated aluminum foil for lithium batteries and the bonding force between the carbon-coated aluminum foil for lithium batteries and the positive electrode active material. The conductive additive can increase the surface roughness of the carbon-coated aluminum foil to a certain extent, so that the positive electrode active material has better contact with the carbon-coated layer 2, thereby bringing about greater intermolecular forces and improving the bonding force between the carbon-coated aluminum foil for lithium batteries and the lithium ion positive electrode active material.

[0076] From the comparison of Examples 1-5, it can be seen that the increase in the amount of conductive additives can increase the conductivity of the carbon-coated aluminum foil for lithium batteries and the bonding force between the carbon-coated aluminum foil for lithium batteries and the positive electrode active material within a certain range. More conductive additives enhance the structural degree of the surface of the carbon-coated aluminum foil and can increase its contact area with the positive electrode active material.

[0077] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and range of equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A highly conductive and highly adhesive carbon-coated aluminum foil, characterized in that: The carbon-coated aluminum foil comprises an aluminum foil substrate (1) and a carbon-coated layer (2), wherein the carbon-coated layer (2) is obtained by coating a conductive slurry on the surface of the aluminum foil substrate (1) and then curing the resulting conductive slurry; The conductive paste is prepared from the following components in parts by weight: Carbon-based conductive carbon black 6-7.5 parts, conductive additive 0.5-2 parts, binder 25-30 parts, auxiliary agent 0.5-1 parts, solvent 61-66.5 parts.

2. The highly conductive and highly adhesive carbon-coated aluminum foil according to claim 1, characterized in that: The carbon-based conductive black is at least one of acetylene black and Ketjen black.

3. The highly conductive and highly adhesive carbon-coated aluminum foil according to claim 1, characterized in that: The conductive additive is at least one of graphene and single-walled carbon nanotubes.

4. The highly conductive and highly adhesive carbon-coated aluminum foil according to claim 1, characterized in that: The binder is polyacrylic acid and modified resins thereof.

5. The highly conductive and highly adhesive carbon-coated aluminum foil according to claim 1, characterized in that: The auxiliary agent is at least one of a cationic wetting and dispersing agent, an anionic dispersing agent and a polymer wetting agent.

6. The highly conductive and highly adhesive carbon-coated aluminum foil according to claim 1, characterized in that: The solvent consists of water and an organic solvent, and the mass ratio of the water to the organic solvent is 3-5:

1.

7. The highly conductive and highly adhesive carbon-coated aluminum foil according to claim 6, characterized in that: The organic solvent is at least one of isopropanol and n-propanol.

8. A method for preparing a highly conductive and highly adhesive carbon-coated aluminum foil according to any one of claims 1 to 7, characterized in that: Specifically include the following steps: Step 1: Add corresponding amounts of the carbon-based conductive carbon black and the conductive additive into a mixing cylinder, and then add corresponding amounts of the auxiliary agent and the solvent, and stir at a speed of 800 rpm for 1-1.5 hours to mix the slurry I; Step 2: Add the corresponding amount of the carbon-based conductive carbon black and the binder to the mixed slurry I, premix and stir at a speed of 1000 rpm until the mixture is uniformly mixed, then add the remaining solvent and mix at a speed of 1500 rpm, and finally grind to obtain the conductive slurry; Step 3: coating the conductive paste on the surface of the aluminum foil substrate (1), and drying at a temperature of 80-150° C. to obtain the carbon-coated aluminum foil.

Citation Information

Patent Citations

  • Lithium ion battery positive electrode sheet containing electric-conduction coating, and preparation method thereof

    CN108511689A

  • Carbon coated aluminum foil with lithium-replenishing function and preparation method thereof

    CN108649231A

  • Carbon-coated aluminum foil and preparation method thereof

    CN109411762A

  • Carbon-coated aluminum foil for lithium battery and preparation method of carbon-coated aluminum foil

    CN114300653A

  • Conductive carbon slurry, positive electrode slurry, and preparation method and application of conductive carbon slurry and positive electrode slurry

    CN114914402A

Cited By

  • Water-based carbon-coated slurry, carbon-coated aluminum foil and preparation method of carbon-coated aluminum foil

    CN121249217A

  • Self-temperature-limiting carbon-coated foil and preparation method thereof

    CN121484076A